2013
DOI: 10.1093/humrep/det013
|View full text |Cite
|
Sign up to set email alerts
|

Poor sleep in PCOS; is melatonin the culprit?

Abstract: The study was funded by the Faculty of Medicine, University of Southampton.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
55
1
6

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(64 citation statements)
references
References 26 publications
2
55
1
6
Order By: Relevance
“…Recent findings suggest that there are circadian rhythm and sleep disturbances in women with diagnosed PCOS [20, 21]. We also observed that women with less than 6 hours of sleep had a 1.7-fold increased risk of having long menstrual cycles (more than 35 days) typical of PCOS, although this association did not reach statistical significance.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…Recent findings suggest that there are circadian rhythm and sleep disturbances in women with diagnosed PCOS [20, 21]. We also observed that women with less than 6 hours of sleep had a 1.7-fold increased risk of having long menstrual cycles (more than 35 days) typical of PCOS, although this association did not reach statistical significance.…”
Section: Discussionmentioning
confidence: 51%
“…It is tempting to speculate that disruption of pulsatile FSH and LH secretion associated with disordered sleep [12, 21, 22] may adversely affect luteinization of granulosa cells, resulting in luteal phase defect [23], which can lead to short menstrual cycles. However, short sleep duration was not significantly associated with any changes in reproductive hormone levels (FSH, LSH, estrogens, androgens) or ovarian variables (volume, anthral follicle counts or AMH).…”
Section: Discussionmentioning
confidence: 99%
“…Admittedly, there are some observations that obese women with PCOS are in the group of increased risk of OSA in comparison with healthy women of reproductive age [18,19], however, there is no apparent correlation between obesity and severity of OSA symptoms [20]. One of the negative factors influencing the quality of sleep among PCOS patients could be diurnal fluctuation of serum melatonin levels [21]. Sleep disturbances in patients suffering from PCOS are described in adult women, but they can be also observed even in adolescent patients [22].…”
Section: Discussionmentioning
confidence: 99%
“…First, the prevalence of obstructive sleep apnea (OSA) was higher in PCOS patients [37], and the mechanisms might be associated with the obesity caused by PCOS-induced metabolic abnormalities [38]. Second, regardless of OSA, studies have shown that the sleep disorders in patients with PCOS might be related to raised nighttime urinary melatonin levels, which are associated with lower sleep quality [39]. In addition, other preliminary hypotheses for sleep disorder among PCOS patients, including the impact of insulin resistance and hyperandrogenemia, have been postulated in the literature [40].…”
Section: Discussionmentioning
confidence: 99%